Upaya intervensi kebidanan dalam menjaga stabilitas suhu tubuh pada bayi baru lahir: Literatur review - Jasmine Nabila; Rahil Azzahra; Bunga Indah Lestari Putri Rismayadi; Sesilya Budiman (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2026)
Newborns, particularly low birth weight (LBW) infants, have an immature thermoregulatory system that increases the risk of hypothermia due to an imbalance between heat production and heat loss. This study aims to analyze the effectiveness of obstetric interventions in maintaining neonatal body temperature stability through kangaroo mother care (KMC), swaddling, and their combination. This study used a literature review method with a descriptive analysis approach of experimental and quasi-experimental studies with pre-test and post-test designs. Data were obtained through observation of neonatal body temperature before and after intervention using digital thermometers, with samples consisting of newborns selected through purposive sampling. The results showed that KMC significantly increased body temperature by an average of 0.47°C, while swaddling helped maintain temperature but did not show a significant increase. The combination of KMC and swaddling produced the most optimal results, with an increase of 0.58°C. In conclusion, KMC, either alone or combined with swaddling, is an effective, simple, and economical intervention to maintain neonatal body temperature stability and prevent hypothermia.